EFFECTS OF HEAVY METALS ON LATA FISH, Channa punctatus, EXPOSED TO THERMAL EFFLUENT WATER - PAL, SARMILA; ROY, SAIKAT; BISWAS, SAYAN; SADHUKHAN, TRINA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
Nowadays the global demand of energy has increased with the advancement of technology and this has been largely met by fossil fuels. For meeting this demand, it causes air, water and land pollution and hampers the ecological balances. Heavy metals present in effluents discharged by fossil fuel-driven industries are the most harmful toxicants for aquatic organisms, and are extremely dangerous for the health of fish. Fishes are used as the bio-indicators, playing a significant role in monitoring heavy metal pollution. Fishes generally take up heavy metals either from food or through the gills and skin. Our study was to investigate the effects of heavy metals released by Bandel Thermal Power Station (BTPS) effluents (untreated) on fish. Excess amounts heavy metals like cadmium, chromium and lead beyond permissible levels were found in the thermal effluent water. For the study of heavy metal contamination, thermal effluent water of Bandel Thermal Power Station was collected and the test organism, lata fish (Channa punctatus) were cultured in this water for seven days in five sets of five different concentrations – 10:0, 9:1, 8:2, 5:5 and 0:10 (Tap water: BTPS water) respectively. Each set contained five fish and the entire trial was replicated thrice. The fish were then sacrificed and blood, liver, kidney, muscle, brain tissues were collected for following biochemical assays - Lipid peroxidation (LPO), Total Thiol content, catalase activity and acetylcholinesterase activity. The ultimate results of this study will allow us to find the toxicity levels of these heavy metals in Channa punctatus and search remedies to prevent this contamination so that a healthy aquatic ecosystem can be maintained.